Prevalence of safety equipment and helmet use among school students commuting to school in South Selangor, Malaysia - Sambasivam, Sivasankar; Abdul Aziz, Adriana; Karuppiah, Karmegam; Zainal Abidin, Emilia; Mohd Tamrin, Shamsul Bahri; Naeini, Hasan Sadeghi; K. C. Mani, Kulanthayan; A. Perumal, Puvanasvaran; Alias, Ayuni Nabilah (Prince of Songkla University, 2020)
A cross-sectional observational study was conducted on the use of helmets and other safety equipment for child pillion riders while going to a school in Sri Serdang, Selangor, Malaysia. The objective of this study was to analyze and report the proportion of children wearing helmets and other safety equipment while riding pillion on a motorcycle. The prevalence of helmet use among the students as pillion riders was low (47.88%) compared to the adults (75.21%). This was unsatisfactory. There is a distinct lack of awareness of the benefits of helmets in helping to save lives and reducing injuries. Hence, there is a need for other safety equipment to provide additional safety protection for child pillion riders to counter the lack of safety equipment use while riding pillion. The Malaysian Ministry of Transport could benefit from this study with the information gained for safety equipment use among school students.